Pulpal inflammation after vital tooth bleaching with 38% hydrogen peroxide - Ardiny Andriani; Juni Handajani; Tetiana Haniastuti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2012)
Background: In-office vital tooth bleaching is a treatment to remove tooth stains. Tooth sensitivity is one of side effect commonly complained by patients receiving this treatment. Purpose: The aim of this study was to examine histological inflammatory cells infiltration of dental pulp after application of 38% H2O2 as a vital tooth bleaching agent. Methods: Under informed consent, a total of 15 premolars from 8 healthy subjects scheduled for orthodontic extraction were used in this study. Thirty eight percent H2O2 was applied on the buccal surface of the treated group. The treated teeth were extracted after 1 hour, 5, 8, and 15 days. All specimens were embedded in paraffin wax, sectioned serially and stained with Hematoxyllin Eosin. Histological specimens were then observed under a light microscope. Results: All treated groups showed a slight disorganization of odontoblasts layer and slight inflammation in the pulp tissue adjacent to the 38% H2O2 application site. The number of polymorphonuclear leukocytes (PMN) had increased significantly 1 hour after application of 38% H2O2 (p<0.05), while macrophages had significantly increased 5 days after the application (p<0.05). The most intense PMN and macrophages infiltration was found 5 days after the application and gradually decreased 8 days after application of38% H2O2. Conclusion: Application of 38% H2O2 as a vital tooth bleaching agent induces acute inflammation in human dental pulp; however, the inflammation will decrease 8 days after the application.Latar belakang: Perawatan pemutihan gigi vital metode in-office merupakan tindakan untuk menghilangkan pewarnaan pada gigi. Salah satu efek samping yang sering dikeluhkan oleh pasien yang menjalani perawatan ini adalah sensitivitas gigi. Tujuan: Penelitian ini bertujuan untuk mengamati infiltrasi sel inflamasi pada pulpa gigi setelah aplikasi H2O2 38% sebagai bahan pemutih gigi. Metode: Sampel penelitian ini berupa 15 gigi premolar yang berasal dari 8 subjek sehat yang akan melakukan pencabutan gigi untuk perawatan ortodontik. Seluruh subjek telah menandatangani informed consent. Hidrogen peroksida 38% diaplikasikan pada permukaan bukal gigi kelompok perlakuan. Gigi kemudian dicabut 1 jam, 5, 8, dan 15 hari setelah aplikasi H2O2 38%. Seluruh spesimen kemudian ditanam dalam parafin, dipotong secara serial dan diwarnai dengan Hematoxillin Eosin. Pengamatan preparat histologis dilakukan dengan menggunakan mikroskop cahaya. Hasil: Hasil penelitian ini menunjukkan gangguan pada lapisan odontoblas dan peradangan pada jaringan pulpa di bawah daerah aplikasi H2O2. Jumlah PMN meningkat secara signifikan (p<0,05) 1 jam setelah aplikasi H2O2 38% sedangkan jumlah makrofag meningkat secara signifikan 5 hari setelah aplikasi hidrogen peroksida 38%. Infiltrasi PMN dan makrofag paling banyak ditemukan 5 hari setelah aplikasi dan menurun secara bertahap 5 dan 8 hari setelah aplikasi H2O2 38%. Kesimpulan: Aplikasi H2O2 38% sebagai bahan pemutih gigi vital dapat menginduksi inflamasi akut pada pulpa gigi manusia, namun, inflamasi akan mereda 8 hari setelah aplikasi.